Control of the Spin Dynamics of Single‐Molecule Magnets by using a Quasi One‐Dimensional Arrangement. Issue 30 (8th May 2018) - Katoh, Keiichi; Yamashita, Satoshi; Yasuda, Nobuhiro; Kitagawa, Yasutaka; Breedlove, Brian K.; Nakazawa, Yasuhiro; Yamashita, Masahiro
Abstract: Magnetic dipole interactions are dominate in quasi one‐dimensional (1D) molecular magnetic materials, in which TbNcPc units (Tb 3+ =terbium(III) ion, Nc 2− =naphthalocyaninato, Pc 2− =phthalocyaninato) adopt a structure similar to TbPc2 single‐molecule magnets (SMMs). The magnetic properties of the [TbNcPc] 0/+ (neutral1 and cationic2 ) with 1D structures are significantly different from those of a magnetically diluted sample (3 ). In particular, the magnetic relaxation time ( τ ) of2 in the low‐temperature region is five orders of magnitude slower than that of3 . Furthermore, the coercivity ( H C ) of2 remained up to about 20 K. The single‐ion anisotropy of Tb 3+ ions in a 1D structure and the magnetic dipole interactions acting among molecules determines the direction of the magnetic properties. These results show that the spin dynamics can be improved by manipulating the arrangement of SMMs in the solid state. Abstract : Tb arranged : The single‐ion anisotropy of Tb 3+ ions in a 1D structure and the magnetic dipole interactions acting among the molecules determine the direction of the spin dynamic properties. These results provide a new molecular design method for improving spin dynamics via the arrangement of the single‐molecule magnets (SMMs) in the crystal.